Conditional recurrence-free survival of clinical complete responders managed by watch and wait after neoadjuvant chemoradiotherapy for rectal cancer in the International Watch & Wait Database: a retrospective, international, multicentre registry study. Issue 1 (January 2021) - Fernandez, Laura M; São Julião, Guilherme P; Figueiredo, Nuno L; Beets, Geerard L; van der Valk, Maxime J M; Bahadoer, Renu R; Hilling, Denise E; Meershoek-Klein Kranenbarg, Elma; Roodvoets, Annet G H; Renehan, Andrew G; van de Velde, Cornelis J H; Habr-Gama, Angelita; et al.
Summary: Background: Watch and wait is a novel management strategy in patients with rectal cancer who have a clinical complete response after neoadjuvant chemoradiotherapy. Surveillance of these patients is generally intensive, because local regrowth (with the potential for salvage) occurs in 25% of patients, and distant metastases occur in 10% of patients. It is unclear for how long these patients should be followed up. To address this issue, we did conditional survival modelling using the International Watch & Wait Database (IWWD), which is a large-scale registry of patients with a clinical complete response after neoadjuvant chemotherapy who have been managed by a watch-and-wait strategy. Methods: We did a retrospective, multicentre registry study using a dataset from the IWWD, which includes data from 47 clinics across 15 countries. We selected patients (aged ≥18 years) with rectal cancer who had a clinical complete response after neoadjuvant chemotherapy, and who were subsequently managed by a watch-and-wait strategy between Nov 25, 1991, and Dec 31, 2015. Patients who had not achieved a clinical complete response or who had undergone any surgical procedure were excluded. The criteria used for defining a clinical complete response and the specific surveillance strategies were at the discretion of each participating centre. We used conditional survival modelling to estimate the probability of patients remaining free of local regrowth or distant metastasis for an additional 2 years after sustaining a clinical complete response or being distant metastasis-free for 1, 3, and 5 years from the date of the decision to commence watch and wait. The primary outcomes were conditional local regrowth-free survival at 3 years, and conditional distant metastasis-free survival at 5 years. Findings: We identified 793 patients in the IWWD with clinical complete response who had been managed by a watch-and-wait strategy. Median follow-up was 55·2 months (IQR 36·0–75·6). The probability of remaining free from local regrowth for an additional 2 years if a patient had a sustained clinical complete response for 1 year was 88·1% (95% CI 85·8–90·9), for 3 years was 97·3% (95·2–98·6), and for 5 years was 98·6% (97·6–100·0). The probably of remaining free from distant metastasis for a further 2 years in patients who had a clinical complete response without distant metastasis for 1 year was 93·8% (92·3–95·9), for 3 years was 97·8% (96·6–99·3), and for 5 years was 96·6% (94·0–98·9). Interpretation: These results suggest that the intensity of active surveillance in patients with rectal cancer managed by a watch-and-wait approach could be reduced if they achieve and maintain a clinical complete response within the first 3 years of starting this approach. Funding: European Registration of Cancer Care, financed by the European Society of Surgical Oncology, the Champalimaud Foundation Lisbon, the Bas Mulder Award, granted by the Alpe d'HuZes Foundation and the Dutch Cancer Society, the European Research Council Advanced Grant, and the National Institute of Health and Research Manchester Biomedical Research Centre.